2016
DOI: 10.1038/mp.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced structural plasticity of medial amygdala stellate neurons and rapid prevention by a candidate antidepressant

Abstract: The adult brain is capable of adapting to internal and external stressors by undergoing structural plasticity, and failure to be resilient and preserve normal structure and function is likely to contribute to depression and anxiety disorders. While the hippocampus has provided the gateway for understanding stress effects on the brain, less is known about the amygdala, a key brain area involved in the neural circuitry of fear and anxiety. Here, in mice more vulnerable to stressors, we demonstrate structural pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 45 publications
2
64
1
2
Order By: Relevance
“…Although stress is well recognized as a key factor in precipitating a variety of disorders (29), including depression, the role of stress in altering the responsiveness to antidepressants is less known. Recently, we showed that stress opens windows of epigenetic plasticity in atrisk individuals (22) and these temporary slots of plasticity can be manipulated by LAC pharmacological intervention to increase resilience, whereby structural plasticity of the medial amygdala stellate neurons plays an important role (30). Here, our findings in endogenously depressed FSL subjected to an acute stress during LAC treatment show that an individual responsiveness to stress needs to be factored in toward the development of better therapeutics.…”
Section: Role Of Stress In Development Of Treatment Resistance In Somementioning
confidence: 69%
“…Although stress is well recognized as a key factor in precipitating a variety of disorders (29), including depression, the role of stress in altering the responsiveness to antidepressants is less known. Recently, we showed that stress opens windows of epigenetic plasticity in atrisk individuals (22) and these temporary slots of plasticity can be manipulated by LAC pharmacological intervention to increase resilience, whereby structural plasticity of the medial amygdala stellate neurons plays an important role (30). Here, our findings in endogenously depressed FSL subjected to an acute stress during LAC treatment show that an individual responsiveness to stress needs to be factored in toward the development of better therapeutics.…”
Section: Role Of Stress In Development Of Treatment Resistance In Somementioning
confidence: 69%
“…This is the first evidence for metabolic signaling to chromatin in the brain and indicates a critical role for this type of signaling in cognitive function. Molecules that affect energy homeostasis, such as the epigenetic molecule acetyl‐ l ‐carnitine that is produced during normal metabolism, affect and hence provide rapid antidepressant‐like activity . These results suggest that metabolic pathways are linked to epigenetic regulation of genes associated with depression.…”
Section: Limitations Future Directions and Concluding Remarksmentioning
confidence: 99%
“…More recently, attention has been given to observing structural changes to the amygdala, the area of the brain involved in fear and anxiety, as a result of prolonged exposure to stress (Lau et al, 2017). This supports findings that stress leads to changes in the brain’s neurocircuitry, with particular regard to the amygdala and pre-frontal region (Mah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%